THE REAL WINNERS : APLIKASI KNOWLEDGE MANAGEMENT DALAM INDUSTRI PERBANKAN NASIONAL - Heri Yuliyanto (Jurnal Vokasi Indonesia, 2016)
Mastery of information technology is important for the banking industry has an oligopoly marketstructure, but does not guarantee a sustainable competitive advantage. To win the competition is not onlydetermined by the technologically and price (interest given), but also factors mastery of knowledge andinformation currently an issue that is very strategic.If a bank uses technology as an advantage its competitiveness, then the advantage will be temporary, because thetechnology has the properties easily imitated. However, if the advantages of information technology along withthe mastery of information and knowledge of quality management, the competitors require greater effort and along time to be able to imitate or duplicate the competitive advantage. Thus the competitive advantage thatwill last longer.Through literature study and analysis of secondary data obtained information that the national bankingmarket outlook is still widespread. In addition, the technology factor is not the major factor is the mainattraction or reason for customers to have a bank account, but the image bank safe is the main reason to haveaccounts.Keyword; Knowledge Mangement, MEA , competitive advantege, competitive strategy